PELATIHAN PEMBUATAN BAKSO IKAN DAN MANAJEMEN USAHA DALAM MENINGKATKAN PENDAPATAN KELUARGA DI KAMPUNG TOBATI - Ratang, Westim; Salle, Hesty Theresia; Tamba, Delima; Munte, Perawati; Tebay, Vince; Marlissa, Elsyan R; Layuk, Paulus K Allo; Salle, Agustinus; Rante, Yohanis (LPPM Universitas Bina Bangsa, 2024)
The training on making fish balls and business management in Tobati Village aims to increase family income through the development of skills and knowledge in the food industry. This program is designed to empower the local community by providing practical skills in making fish balls as well as knowledge in business management. Through this training, it is hoped that participants can develop fish ball businesses independently, improve product quality, and optimize local marketing. The results of this training are expected to make a significant contribution to increasing family income, as well as improving welfare and economic development in Tobati Village